Study on the influence mechanism of Mg2+ modification on vermiculite thermal expansion based on molecular dynamics simulation. Issue 5 (1st April 2020) - Feng, Jinpeng; Liu, Meng; Fu, Linzong; Ma, Shaojian; Yang, Jinlin; Mo, Wei; Su, Xiujuan
Abstract: The thermal insulating performance of expanded vermiculite is closely related to expansibility. A novel method of Mg 2+ modification was proposed to improve the vermiculite expansion ratio. The modification process was characterised by energy dispersive X-Ray spectroscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, thermogravimetric-differential scanning calorimeter and scanning electron microscopy. Moreover, the thermal expansion experiment was performed to investigate the expansion behaviours of Raw-V and Mg–V samples at various temperatures. The result indicated that the introduction of Mg 2+ could increase the vermiculite interlayer water content through hydration interaction, and the expansion ratio increased 13.7% under the heating temperature of 900 °C after modification. To explain the interaction of magnesium ion and water molecules, a molecular dynamics model was developed, and the simulation results were validated using the binding energy calculation. The results of this study can provide a new perspective and theoretical guidance for the commercial process of vermiculite expansion.